The effectiveness of direct versus indirect restoration techniques following canal therapy - Alshargawi, Waleed K.; Tawhari, Feras E.; Aladwani, Ameerah S.; Hassanein, Zyad A.; Fageeh, Sahar N.; Almeshrf, Ahmed W.; Alamani, Saud F.; Neyaz, Aymen A.; Albalbisi, Asraa W.; Alsadiq, Belal M.; Alasmari, Abdulrahman A. (International Journal Of Community Medicine And Public Health, 2024)
The restoration of endodontically treated teeth is a critical aspect of dental practice, with the choice between direct and indirect restoration techniques being central to optimizing clinical outcomes. Direct restorations, such as composite resins, offer advantages in terms of cost, time efficiency, and preservation of tooth structure. However, their long-term performance, particularly in posterior teeth, may be compromised by issues such as marginal leakage, wear, and discoloration. Indirect restorations, including crowns, onlays, and inlays, provide enhanced durability, fracture resistance, and aesthetic outcomes, particularly for teeth that have undergone significant structural loss. These restorations, often made from ceramics or metals, offer superior longevity but come with higher costs and longer treatment times. The aesthetic performance of restorations plays a significant role in patient satisfaction. While direct restorations allow for immediate aesthetic adjustments and are generally more affordable, they may suffer from discoloration and wear over time. Indirect restorations, particularly porcelain-based options, offer better color stability and natural appearance, making them a preferred choice for patients with high aesthetic demands. Cost-effectiveness is another critical factor influencing clinical decision-making. While direct restorations are more affordable initially, their long-term cost-effectiveness may be compromised by the need for repairs or replacements. Indirect restorations, despite their higher upfront cost, often prove to be more economical in the long run due to their durability and reduced need for maintenance. The decision between direct and indirect restoration techniques should be individualized, considering factors such as tooth location, the extent of damage, aesthetic requirements, and financial constraints. A comprehensive evaluation of these factors, along with clear communication with the patient, is essential for achieving optimal clinical outcomes. Indirect restorations generally offer better long-term performance, particularly for heavily compromised teeth, while direct restorations remain a viable option for cases where cost and time efficiency are prioritized.